2008
DOI: 10.1598/rrq.43.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Home Storybook Reading in Primary or Second Language With Preschool Children: Evidence of Equal Effectiveness for Second‐Language Vocabulary Acquisition

Abstract: This study examined how providing either primary‐ or English‐language storybooks for home reading followed by classroom storybook reading and vocabulary instruction in English influenced English vocabulary acquisition. Participants in the study were preschool children (N = 33), from low socioeconomic status families, whose primary language was either Hmong or Spanish. There were two 6‐week sessions of home combined with classroom storybook reading. Children were randomized to either a primary‐ or English‐langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
2
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 52 publications
4
114
2
22
Order By: Relevance
“…In a study of one such approach, Roberts (2008) examined the efficacy of a bilingual storybook reading intervention wherein parents (all of whom were ELLs, L1 was Spanish or Hmong, and of low SES) received brief training in read-aloud practices with a storybook in L1 or L2. Preschoolers were randomly assigned to one of two treatment groups (TGs; L1 or L2 storybook) using a crossover design.…”
Section: Flps That Provide Instruction In L1 and L2mentioning
confidence: 99%
“…In a study of one such approach, Roberts (2008) examined the efficacy of a bilingual storybook reading intervention wherein parents (all of whom were ELLs, L1 was Spanish or Hmong, and of low SES) received brief training in read-aloud practices with a storybook in L1 or L2. Preschoolers were randomly assigned to one of two treatment groups (TGs; L1 or L2 storybook) using a crossover design.…”
Section: Flps That Provide Instruction In L1 and L2mentioning
confidence: 99%
“…Los resultados de estudios sobre efectos de factores ambientales en el proceso de alfabetización indican que en el contexto de la familia es relevante el rol facilitador del aporte de experiencias literarias en el hogar (Dickinson & Tabors, 2002;Porta & Difabio, 2011;Roberts, 2008).…”
Section: Conclusiónunclassified
“…Toda actividad que padres o cuidadores desarrollen en casa con los niños tendrá sin duda un efecto en sus experiencias de aprendizaje futuras, entre ellas las relativas a aprendizajes escolares tales como la lectura y la escritura. La lectura de cuentos y las interacciones verbales que acaecen en el hogar entre padres y/o cuidadores y los niños constituyen una excelente oportunidad para que estos aprendan habilidades básicas que necesitan para iniciarse en el proceso de alfabetización, entre ellas, habilidades de conciencia fonológica, enriquecimiento del vocabulario y comprensión lectora (Dickinson & Tabors, 2002;Porta & Difabio, 2011;Roberts, 2008).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Specifically, it has been shown that there is a positive impact of parental involvement in literacy in one's native language on school readiness and success. Roberts found that primary-language storybook reading in the home was as effective as home storybook reading in English for promoting English vocabulary acquisition in preschool students who are learning English; children who received storybooks in their primary language performed significantly better on English recognition of target storybook words than English language learning students who read books at home in English [18].…”
Section: Introductionmentioning
confidence: 99%